(untitled) (Vietnam Journal of Community Medicine, 2022)
Aim: (1) Evaluation results on VAS and KOOS scores after 12 months of treatment of osteoarthritis patients with platelet-rich plasma (PRP) therapy; (2) Evaluation results on ultrasonography and MRI after 12 months of treatment of osteoarthritis patients with platelet-rich plasma (PRP) therapy. Subject and Method: Intervention study on 40 patients diagnosed with stage 2 and 3 osteoarthritis according to Kellgren and Lawrence, who were intervened by PRP. Evaluation on clinical, ultrasound and magnetic resonance after 12 months of follow-up. Result: VAS score of the patients before the intervention was 6.53±1.81, after 12 months of the intervention it was 3.93±2.74, KOOS score of the patients before the intervention was 46.27±13, 62, after 12 months of intervention was 83.09±13.14 (P<0.05). On ultrasound, the average thickness of articular cartilage of patients before intervention was 1.74±0.39, after 12 months of intervention, it was 1.83±0.36 with improved cartilage thickness over time (P <0.05), the patient had a reduced rate of synovial membrane proliferation (P<0.05). On magnetic resonance, after PRP treatment, there was an improvement in the lesions of the medial condyle of the femur, the outer condyle of the femur, the patellar surface, the condylar surface and the lateral tibial plateau (P<0.05). Conclusion: The treatment of knee osteoarthritis with platelet-rich plasma is effective in improving the cartilage thickness on ultrasound and magnetic resonance, thereby improving the mobility of the knee joint.